Mutation abundance affects the therapeutic efficacy of EGFR-TKI in patients with advanced lung adenocarcinoma: A retrospective analysis. Issue 8 (3rd August 2018) - Wang, Huijuan; Zhang, Mina; Tang, Wanyu; Ma, Jie; Wei, Bing; Niu, Yuanyuan; Zhang, Guowei; Li, Peng; Yan, Xiangtao; Ma, Zhiyong
ABSTRACT: Purpose : To investigate the influence of mutation abundance and sites of epidermal growth factor receptor (EGFR) on therapeutic efficacies of EGFR-tyrosine kinase inhibitor (EGFR-TKIs) treatments of patients with advanced non-small cell lung carcinoma (NSCLC). Methods : EGFR mutational sites and mutation abundance were analyzed by amplification refractory mutation system (ARMS) in paraffin-embedded tissue sections taken from primary or metastatic tumors of 194 NSCLC patients. Results : The median progression-free survival (PFS) time of the enrolled patients was 9.3 months (95% CI, 8.2–10.8 months). The PFS was significantly different with EGFR gene mutation abundance after EGFR-TKI therapy ( P = 0.014). The median PFS was significantly longer when the cut-off value of EGFR mutation abundance of exon 19 or exon 21, and solely exon 19 was > 26.7% and 61.8%, respectively. For patients who received EGFR-TKI as first-line treatment, the median PFS was significantly longer in the high mutation abundance group than in the low mutation abundance group (12.7 vs 8.7 months, P = 0.002). Conclusion : The PFS benefits were greater in patients with a higher abundance of exon 19 deletion mutations in the EGFR gene after EGFR-TKI treatment and first line EGFR-TKI treatment led to improved PFS in high mutation abundance patients.